Pengaruh Penerapan Strategi Pembelajaran Learning Start with a Question terhadap Hasil Belajar Siswa pada Mata Pembelajaran Informatika di SMAS Pembangunan Bukittinggi - Desriana Desriana; Zulfani Sesmiarni (MASALIQ, 2026)
The low cognitive learning outcomes of tenth-grade students at SMAS Pembangunan Bukittinggi, as indicated by the large number of students who had not yet achieved the Minimum Criteria for Learning Objective Achievement (KKTP), demonstrate the need to implement a learning strategy that promotes students’ active engagement. This study aimed to analyze the effect of implementing the Learning Starts with a Question strategy on students’ learning outcomes in the Informatics and Computer subject. The study employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The research sample was selected through purposive sampling and comprised an experimental group and a control group. Data were collected using an objective test administered as a pretest and posttest. The results showed that the mean learning outcome score of the experimental group was 82.24, which was higher than that of the control group at 72.80. The hypothesis test yielded a significance value of 0.033 (p < 0.05); therefore, the null hypothesis was rejected, and the alternative hypothesis was accepted. These findings indicate that implementing the Learning Starts with a Question strategy had a significant effect on improving students’ learning outcomes. Thus, this strategy can be used as an alternative instructional approach that promotes student engagement and improves learning achievement in the Informatics and Computer subject.